Histological analysis of resistant and susceptible eucalyptus plants inoculated with Ceratocystis fimbriata - Firmino, Ana Carolina [UNESP]; Tozze, Hugo José [UNESP]; Viana, Camila Maciel [UNESP]; Soliman, Everton Pires; De Souza, Izabel Christina Gava; Da Silva, Magali Ribeiro [UNESP]; Tristão, Larissa Escalfi [UNESP]; Furtado, Edson Luiz [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2018)
The genus Ceratocystis includes several species distributed throughout the world. A plant infected with this fungus presents as primary symptoms the darkening of the vascular system and as secondary symptoms wilt, dryness and death of the plant, due to the collapse of the xylem caused by the fungus. These symptoms are typical of water stress and occur in diseased plants as the result of the development of the pathogen inside their vessels and also by plant defense mechanisms that blocks xylem vessels. The present work had the objective of analyzing the structural and biochemical reactions that could be related to eucalyptus plants resistance to Ceratocystis. To observe the structural and biochemical reactions of eucalyptus plants colonized by the fungus, eucalyptus plants of E. Grandis (Clone C3 resistant to fungus and Clone C10 susceptible to fungus) were inoculated with a C. Fimbriata isolate. After inoculation, inoculated stems fragments were collected (7 and 21 days after inoculation), fixed in Karnovsky and processed by historesin polymerization. Different techniques were used to visualize gums and gels, starch grains, arginine, lignins and tyloses. Tyloses, gels and gums were observed in all plants inoculated with Ceratocystis. Lignin accumulation was observed only in resistant plants. Starch and arginine were observed in all worked plants. These results suggest that the eucalyptus resistance to the Ceratocystis fungus may be linked to the accumulation capacity of liguinins in the cells, since this structure was only visualized in resistant plants inoculated with the fungus.
Análise histológica de plantas de eucalipto resistentes e suscetíveis inoculadas com Ceratocystis fimbriata
Keywords: Eucalyptus wilt; Forest pathology; Resistance; Vascular disease